(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2020)
The term post truth was chosen as the word of the year by the Oxford dictionary in 2016. Today we see the proliferation of the term fake news as well as the dissemination of alternative views to science, such as “flat Earth”, integrative therapies, and anthropogenic global warming denial. Usually, postmodernism is blamed for subsidizing such movements theoretically. In the present article, we defend the thesis that both, the official discourse of science (modernist discourse) and its main criticisms (including postmodernism) seem to be propositions that sustain the contemporary scenarios of production and proliferation of post-truths. From Bruno Latour’s Science Studies, we reflect on the metaphysical basis of such perspectives and present an explanation to the formation of the “post-truth” through two different mechanisms, i.e, the presentation of a reduced vision of nature of science and the erasure of the network that sustains scientific propositions. We also defend that Science Education can adopt an alternative metaphysical basis, developed by Latour and collaborators in dialogue with different philosophical and sociological currents, contributing to the formation of citizens able to have a critical position in the contemporary socioscientific scenario.